1970
DOI: 10.4314/ijest.v7i1.3
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on effect of process parameters in deep drawing using Taguchi technique

Abstract: The effects of various deep drawing process parameters were determined by experimental study with the use of Taguchi fractional factorial design and analysis of variance for AA6111 Aluminum alloy. The optimum process parameters were determined based on their influence on the thickness variation at different regions of the blank material. Three important process parameters i.e., punch nose radius, die shoulder radius and blankholder force were investigated in this study. Plan of experiments based on Taguchi's t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
0
28
0
1
Order By: Relevance
“…Each process variable has three levels, as presented in Table 1. Reddy et al [10] used the Taguchi fractional factorial design and analysis of variance to find the optimum process parameters and their influence on the thickness variation at different regions of the blank material for AA6111 aluminum alloy. Another similar example was reported by Raju [11], where he used Taguchi's signal-to-noise ratio and observed that the die shoulder radius has a significant influence on the thickness distribution of the deep-drawn cup of AA6061 sheet followed by the blank holder force and punch nose radius.…”
Section: Methodsmentioning
confidence: 99%
“…Each process variable has three levels, as presented in Table 1. Reddy et al [10] used the Taguchi fractional factorial design and analysis of variance to find the optimum process parameters and their influence on the thickness variation at different regions of the blank material for AA6111 aluminum alloy. Another similar example was reported by Raju [11], where he used Taguchi's signal-to-noise ratio and observed that the die shoulder radius has a significant influence on the thickness distribution of the deep-drawn cup of AA6061 sheet followed by the blank holder force and punch nose radius.…”
Section: Methodsmentioning
confidence: 99%
“…graph) must be hand written/drawn. 6. Discussion of results in light of the theoretical predictions.…”
Section: Report Formatmentioning
confidence: 96%
“…Research with the experimental design method of Taguchi and Anova to analyze the effect of the punch radius, die radius, and blank holder force on the thickness of the blank sheet being drilled into a cup cylinder has been carried out by [15]. In this study, an experimental method is proposed to understand the effect of various parameters on the variation of the thickness of the cup cylinder formed by the deep drawing process.…”
Section: Materials Thickness Ratio (T R ) and 2 Drawing Ratio (M)mentioning
confidence: 99%